Development of a novel CO2 splitting fixed-bed reactor based on copper-doped cerium oxide. Issue 1 (1st December 2022) - Milanese, Marco; Manzo, Andrea; Colangelo, Gianpiero; Risi, Arturo de
Abstract: Global warming has received widespread attention in recent years due to the accumulation of carbon dioxide. Looking at the current energy landscape, new technologies must be developed to reduce CO2 emissions. The present work is aimed to develop and test a new prototype of an innovative reactor for the conversion of CO2 into CO, operating according to a two-phase thermochemical cycle. The innovative and main aspect of this study was the use of a reactor coupled with a new type of catalyst, a copper-doped cerium oxide (Cuδ+2 Ce(1-δ) O2 ), which allowed to decrease the temperature of the reaction up to 850°C, much lower than the models present in the literature, tested on 1300/1400°C and even beyond.